The Development of Settler Agriculture in British Africa Revisited: Estimating the Role of Tenant Labour in Southern Rhodesia, c. 1920-1960 - Erik Green (African Economic History Network (AEHN), 2016)
In this paper I use primary and secondary sources to quantify the role of tenant labour on settler farms in colonial Africa, using Southern Rhodesia as a case in point. My findings show that the rise of wage labour did not mark the end of labour tenancy, as has been assumed in previous literature. On the contrary, the two forms of labour co-existed. The results find support in the theoretical literature on agrarian labour contracts as well as from studies on farm labour on large farms in pre-industrial Europe and America. This literature has been surprisingly neglected in studies of rural labour relations in colonial Africa. Based on my estimates I revise the fundamental question of the role of access to and control of indigenous labour in the growth of European settler agriculture in Africa. In contrast to previous research, I argue that the rise of wage labour was a response to settler farmers' limited capacity to control tenant labour rather than a sign of the superiority of agrarian capitalist relations of production.
Keywords: N17; N27; N37; N47; 330; Settler agriculture; Africa; labour; Southern Rhodesia